A COMPARATIVE ANALYSIS OF POETIC DEVICES: ALLITERATION, ASSONANCE, AND ENJAMBMENT IN ENGLISH AND UZBEK POETRY - Karimova, Ozodaxon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This research compares the stylistic purposes and cultural systems of three poetic devices—enjambment, assonance, and alliteration—across English and Uzbek poetry. Ten exemplary poems in every language are compared within the research to note how such strategies enhance rhythm, emotion, and thematic efficiency. They are generally used in Uzbek poetry for oral tradition rhythm and memorability but used in English poetry to establish mood, attract attention to the issue, and initiate melody. Enjambment is uncommon in traditional Uzbek poetry due to formal metrical forms, but increasingly used in modern poetry. This comparative methodology brings to the fore the liaison between language, culture, and sense of aesthetics inasmuch as it places before us the universal as well as culturally specific poetic devices. This book encourages cross-cultural literary study and suggests further research studies on poetical devices across cultures.